Relationships and determinants of adoption of sustainable land management technologies in Eastern and Southern Highlands of Ethiopia - Temesgen, Alemayehu; Yousuf, Jemal; Shambel, Getachew; Seyoum, Chanyalew (Brawijaya University, 2024)
Degraded land is a major danger to agricultural productivity and food security in Ethiopia. Sustainable land management technologies (SLMTs), through targeted interventions, have been applied to address this problem. Notwithstanding some of the known agricultural and environmental benefits connected with the adoption of some SLMTs, the adoption rate remains below expectations. Therefore, this study aims to analyze the relationships and determinants of the adoption of SLMTs in eastern and southern Ethiopia. Data were collected from 384 sampled households selected using multi-stage sampling techniques. Descriptive statistics and multivariate probit (MVP) model were used to analyze data. Estimated results of MVP revealed that the adoption of SLMTs is positively and significantly influenced by education level, livestock, membership in a social group, extension contacts, access to SLM information, training, credit, land tenure, and slope, while age, farm distance, and the number of active family members due to youth migration abroad had negative effects. The widely adopted SLMTs on farmlands were inorganic fertilizer (49.5%), soil bunds (48.4%), bench terraces (47.2%), intercropping (46.1%), and manure (38%). This study concluded that farmers invested a blend of SLMTs, some of which complemented and others substituted for one another. Therefore, policy-makers and planners should focus on fortifying human and local institutions’ capacity to implement SLM and consider SLM technology interdependencies before communicating with farmers.